Drug Resistance and the Prevention Strategies in Food Borne Bacteria: An Update Review - Fataneh Hashempour-Baltork; Hedayat Hosseini; Saeedeh Shojaee-Aliabadi; Mohammadali Torbati; Adel Mirza Alizadeh; Matin Alizadeh (Tabriz University of Medical Sciences, 2019)
Antibiotic therapy is among the most important treatments against infectious diseases and has tremendously improved effects on public health. Nowadays, development in using this treatment has led us to the emergence and enhancement of drug-resistant pathogens which can result in some problems including treatment failure, increased mortality as well as treatment costs, reduced infection control efficiency, and spread of resistant pathogens from hospital to community. Therefore, many researches have tried to find new alternative approaches to control and prevent this problem. This study, has been revealed some possible and effective approaches such as using farming practice, natural antibiotics, nano-antibiotics, lactic acid bacteria, bacteriocin, cyclopeptid, bacteriophage, synthetic biology and predatory bacteria as alternatives for traditional antibiotics to prevent or reduce the emergence of drug resistant bacteria.